COMMON FEATURES OF THE MAIN CHARACTERS OF SOMERSET MAUGHAM AND ABDULLA KAHHOR’S SHORT-STORIES - Sheraliyeva Dildora Abduvaxob qizi (Western European Studies, 2025)
This article explores the common features of the main characters in the short stories of Somerset Maugham and Abdulla Kahhor. Despite their different cultural and historical backgrounds, both authors portray protagonists with rich psychological depth, moral ambiguity, and inner conflicts driven by societal norms. The study highlights how both writers present characters who struggle with alienation, adapt to social pressures, and ultimately reflect the universal aspects of the human condition. The paper emphasizes the similarities in character development, thematic concerns, and narrative techniques employed by Maugham and Kahhor, offering a comparative perspective on English and Uzbek short story traditions of the 20th century.
Keywords: Somerset Maugham; Abdulla Kahhor; short stories; main characters analysis